Specialized mental healthcare use for common mental disorders and prescription of antidepressants before and during the COVID-19 pandemic among working-age refugees and Swedish-born individuals – a nationwide register-based study - Vera Atarodi; Ellenor Mittendorfer-Rutz; Daniel Morillo-Cuadrado; Roberto Mediavilla; Mireia Felez-Nobrega; Anna Monistrol-Mula; Pierre Smith; Vincent Lorant; Papoula Petri-Romão; Marit Sijbrandij; Anke B. Witteveen; Irene Pinucci; et al. (BMC Public Health)
Abstract Background It is known that refugees have an elevated risk of common mental disorders (CMDs, including depression, anxiety, and stress-related disorders). The effect of the coronavirus disease pandemic on healthcare use due to CMDs in refugees is yet unknown, especially in socioeconomically deprived groups. We conducted a population-wide study comparing specialized healthcare use for CMDs and antidepressant prescriptions before and during the pandemic in refugees and Swedish-born, and investigated differences by labor market marginalization and education. Methods An interrupted time series analysis of quarterly cohorts (2018.01.01–2021.12.31) of all refugees and Swedish-born, aged 19 to 65 was applied. Information on outcome measures and covariates were linked individually from administrative registers. We applied interrupted time series and estimated incidence rate ratios (IRR) of the incidence rates (IR) and their corresponding confidence intervals (CI) before and during the pandemic. Results A total of 4,932,916 individuals, of whom 488,299 (9.9%) were refugees, were included at baseline. We observed a 3% (95% CI: 1%, 5%) quarterly increase in trends of healthcare use due to CMDs in refugees, but no changes in Swedish-born individuals. The IRRs were larger in refugees whose labor market position was marginalized (IRR: 6%, (3%, 9%)), and refugees with low education level (IRR: 4% (1%, 7%)). There were no substantial changes in antidepressant prescription. Conclusion Refugees, especially those already in a marginalized position, had increased CMD-related mental healthcare use during the pandemic. Strategies to meet the mental health care needs of marginalized refugees are of outmost public health importance.